2004
DOI: 10.1590/s1516-35982004000300001
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia quantitativa da folha e do colmo de Brachiaria brizantha (Hochst. ex A. Rich.) Stapf e B. humidicola (Rendle) Schweick

Abstract: Anatomia Quantitativa da Folha e do Colmo deABSTRACT -The forage digestion characteristics can better be understood when associated with studies of tissue anatomy of forage species. Aiming at new focus to this issue, the area of several tissues present in leaves and stems of B. brizantha and B. humidicola, were determined at three different regions of the plant. The assay was carried out at greenhouse, with plants growing in pots with sterilized sand, receiving nutritive solution of macro and micronutrients. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…There are many works using that method as a complementary contribution to evaluate the digestibility potential of leaf tissues. Brito, Rodella, and Deschamps (2004) evaluated the anatomy of leaves at different insertion levels in plants of Brachiaria brizantha and B. humidicola and found larger area of lignified tissues related to the lower digestibility of B. brizantha. Bauer, Gomide, Silva, Regazzi, and Chichorro (2008) evaluated the influence of anatomical traits upon the nutritive value of molasses grass (Melinis minutiflora Pal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many works using that method as a complementary contribution to evaluate the digestibility potential of leaf tissues. Brito, Rodella, and Deschamps (2004) evaluated the anatomy of leaves at different insertion levels in plants of Brachiaria brizantha and B. humidicola and found larger area of lignified tissues related to the lower digestibility of B. brizantha. Bauer, Gomide, Silva, Regazzi, and Chichorro (2008) evaluated the influence of anatomical traits upon the nutritive value of molasses grass (Melinis minutiflora Pal.…”
Section: Introductionmentioning
confidence: 99%
“…and concluded that lower digestibility coefficients were related to high proportion of xylem and sclerenchyma. In addition, plant anatomy is useful for the comparison of different species, cultivars and the forage maturity (Brito et al, 2004). Furthermore, the decline of nutritive value upon maturity is due to increased lignification (Brito et al, 1999;Paciullo, Gomide, Silva, Queiroz, & Gomide, 2002;Paciullo, 2002;Carvalho & Pires, 2008;Pariz et al, 2010;Medeiros, Pinto, Castro, Rezende, & Lima, 2011;Mauri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, DMD correlates negatively with NDF, ADF, vascular tissue, and sclerenchyma, as is mentioned in several reports of C4 species. [6][7][8] Brito et al 51 evaluated the anatomy of leaves at different insertion levels in plants of Brachiaria brizantha and Brachiaria humidicola at 70 days growth and found a larger area of lignified tissues related to lower digestibility. Moreover, Batistoti et al 13 showed that a high proportion of fiber was negatively correlated with dry matter digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the authors found that cv. IACSP95-5000 has a wide range of chemical and structural factors that may be associated with low fiber digestibility (Akin1989; Queiroz et al 2000;Brito et al 2004;Valente et al 2011).…”
Section: Structural Features Of the Sugarcanementioning
confidence: 99%